ANALISIS DAN KARAKTERISASI NANOPARTIKEL PERAK (AgNPs) UNTUK MENDETEKSI KLORAMFENIKOL DENGAN METODE KOLORIMETRI - Sari, Ros Mita; Arif, Moh. Syaiful; Yusuf, Bohari (Jurusan Kimia FMIPA UNMUL, 2022)
Synthesis of silver nanoparticles (AgNPs) with the addition of Trisodium citrate 1% as a reducing agent and stabilizer in AgNO3 by chemical reduction. The obtained AgNPs were characterized using UV-Vis Spectrophotometer, PSA (Particle Size Analyzer) and TEM (Transmission Electron Microscopy). Concentration optimum gNPs is 1 mM AgNO3 with the addition of 6 mL of Trisodium citrate 1% at heating temperature 85OC for 13 minutes stirring. Characterization of AgNPs with TEM resulted in average particle size of 46,5 nm with various shapes of triangels, rectangles, hexagons and rounds. The synthesized silver nanoparticles (AgNPs) were used for analysist chloramphenicol. The measurement results of the calibration curve show that the linear equation y = 0,0078x + 0,8623 with a correlation value of r 0,9954. The results of the validation form precision values is 0,54759 % has met a good precision, namely KV 2%.